Manual de búsqueda documental y práctica bibliográfica / José Antonio Cordón García, Jesús López Lucas, José Raúl Vaquero Pulido. Madrid : Pirámide, 1999. 238 p. : il. (Ozalid). ISBN: 84-368-1202-6 (Información, cultura y sociedad, 2004)
Reseña.